Effect of air drying process on the physicochemical, antioxidant, and microstructural characteristics of tomato cv. Chonto (2017)
The tomato is a Solanaceae plant which globally has the second highest production rate, making it one of the most important vegetative products in global production and consumption. Furthermore, the tomato is valued for its antioxidant components, most notably vitamin C, phenolic components and carotenoids such as lycopene and β-carotene. The present study aimed to evaluate the influence of three drying temperatures (50, 60 and 70°C) on the physicochemical, microstructural, and antioxidant characteristics of the tomato. The study analyzed the parameters for color using the coordinates CIE L* a* b* and texture analysis using the methodology of TPA for instrumental analysis and PCA for data analysis, antioxidant capacity and content were measured by spectrophotometric methods and microestructure by Scanning Electron Microscope. The results showed changes in color for the tomato samples treated with 70°C. In addition, the texture of the samples treated at 60°C presented significant differences from the samples dried at 50 and 70°C regarding the fracturability, having a crispier texture and good balance between masticability and hardness. The total carotenoid content increased with the drying process, while the total phenol content decreased. The antioxidant activity was not affected by the temperature variation with respect to the fresh tomato.